2020
DOI: 10.3390/medicina56110558
|View full text |Cite
|
Sign up to set email alerts
|

Major Clues and Pitfalls in the Differential Diagnosis of Parathyroid and Thyroid Lesions Using Fine Needle Aspiration Cytology

Abstract: Background: It is difficult to distinguish parathyroid lesions (PLs) from thyroid lesions using fine needle aspiration cytology (FNAC) because of their proximity and their similar cytomorphological features. Methods: FNAC smears of 46 patients with pathologically proven PLs that were histologically diagnosed as parathyroid adenoma (PA, n = 35), parathyroid hyperplasia (PH, n = 3), atypical parathyroid adenoma (APA, n = 1), and parathyroid carcinoma (PC, n = 7) were retrospectively reviewed and analyzed. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…At our department, we use ICC using antibodies against TTF1 and PTH, but previous work indicate that also GATA3 may facilitate the discrimination between these two tissue types 15 . Moreover, in terms of diagnostic pitfalls when dealing with FNAC on parathyroid lesions, previous studies highlight the risk of falsely diagnosing a papillary thyroid carcinoma 2,3,8 since the presence of tight, three‐dimensional clusters with a central capillary can be seen in smears from a parathyroid lesion—a pattern that may be interpreted as papillary formations. Previous studies have suggested the phenomenon to be correlated to a hypervascular lesion detected on color Doppler sonogram 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At our department, we use ICC using antibodies against TTF1 and PTH, but previous work indicate that also GATA3 may facilitate the discrimination between these two tissue types 15 . Moreover, in terms of diagnostic pitfalls when dealing with FNAC on parathyroid lesions, previous studies highlight the risk of falsely diagnosing a papillary thyroid carcinoma 2,3,8 since the presence of tight, three‐dimensional clusters with a central capillary can be seen in smears from a parathyroid lesion—a pattern that may be interpreted as papillary formations. Previous studies have suggested the phenomenon to be correlated to a hypervascular lesion detected on color Doppler sonogram 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Primary hyperparathyroidism (pHPT) is recognized as symptomatic or asymptomatic hypercalcemia and high to borderline high levels parathyroid hormone (PTH) in the blood. If secondary reasons for hyperparathyroidism have been ruled out (such as renal failure), the cause is one or several parathyroid neoplasms, such as an adenoma (single or multiple) or carcinoma (almost always single nodules) 1,2 . Traditionally, patients were surgically treated using a bilateral neck exploration approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parathyroid tumours occasionally have to be distinguished from thyroid neoplasms because of close anatomic relation [137] between both glands, including occasional intrathyroidal location of normal parathyroid gland or parathyroid carcinoma. The histogenetic diagnosis is difficult also in fine needle aspiration cytology [138].…”
Section: Cd44mentioning
confidence: 99%
“…Currently, only few studies have targeted the microenvironment of parathyroid tumours although there are some direct or indirect reports on macrophages [176,177] that were formerly known as a confounding factor in cytology [138,178], and angiogenesis evaluated via morphology or radiological imaging [179,180]. Similarly, scant studies are performed on systemic inflammatory reaction in patients diagnosed with parathyroid tumours [181].…”
Section: Tumour Microenvironmentmentioning
confidence: 99%